An experimental study on mechanical properties of concrete containing steel and polypropylene fibers at high temperatures - Madjid Gholhaki (Iranian Society of Structrual Engineering (ISSE), 2017)
The use of fibers in concrete improves strength, ductility and durability of concrete. Concrete has fireproofing properties, but rebars are the most important concern of reinforced concrete structures in the event of fire outbreak. Therefore, one of the recommendations to reduce these risks is the use of alternative materials like fibers. In this paper, the effects of different temperatures on the mechanical properties of concrete with different cement contents containing steel and polypropylene fibers were studied. Although the samples were placed under temperatures of 25, 100, 250, 500 and 700 °C, the results revealed that the effects of fire on concrete containing steel fiber is more damaging, and also the compressive and bending strengths at 25 °C and tensile strength at 250 °C have the maximum values.